Feedback on paediatricians' performance from parents and carers: SSASG pilot. (24th May 2012) - McGraw, M; Fellows, S; Foard, L; Lee, L; Millar, H; Muir, G; Thomson, APJ; Uddin, S; Watt, J
Abstract : Aims: Having already demonstrated that the Paediatric Carers of Children Feedback (PaedCCF) tool is reliable and valid in a national pilot study with consultant paediatricians1 the aim of this second pilot was to determine if the tool is also useful with SSASG doctors not on the specialist register. Methods: Self-selecting participants were each sent 35 forms to be distributed locally to carers of children for completion following outpatient consultations. RCPCH-analysed feedback returned to doctors included self assessment scores, carer scores, and overall cohort scores for each question. Qualitative comments were also included. Paediatricians' views on feasibility were sought before and after receiving feedback by online survey. Results: 58 consultants returned 1512 forms (mean 26 per doctor). All doctors scored highly (mean ratings >4.1 out of 5). Aggregate whole-instrument rating was 4.42 (SD = 0.63). Self assessment scores (mean 3.71, SD 0.45) were lower than carer scores (mean 4.42, SD 0.63) p<0.001. White doctors scored more highly than non white doctors (p<0.001) but the difference in the mean was small. Carers who had seen the doctor more than 10 times rated doctors higher than those that had seen the doctor 1-4 times (p<0.001); scores across individual questions were highly correlated (reliability of 0.97 using Cronbach's Alpha) which justifies the use of an aggregate score. Fewer than 25 consultation ratings were needed for good reliability (D-study). 93.4% of consultants found the tool acceptable as evidence for revalidation. Use of pre-paid envelopes assisted some doctors but concerns continue to be expressed about need for administrative support for a paper based feedback tool. Conclusion: This second pilot extends the range of the use of PaedCCF as evidence to support revalidation. Data from this pilot has also allowed a revision of the number of forms required for reliability to be reduced to 20.